Synthesis of β3-Amino Acid Derivatives via the Regioselective Carbozincation of Ynamides and Subsequent Asymmetric Hydrogenation - Ohrui, Sayaka; Matsui, Sugako; Yoshida, Keisuke; Oshida, Noriko; Tayu, Masanori; Saito, Nozomi (Synthesis, 2026)
β-Amino acids are key constituents of various bioactive molecules, pharmaceuticals, and natural products, thereby highlighting their importance in organic chemistry. A novel synthetic method was developed for β3-amino acid derivatives based on the use of ynamides bearing ester moieties. Initially, the Cu-catalyzed regioselective carbozincation of these ynamides afforded β-aminoacrylic acid esters bearing a substituent at the β-position. Subsequent asymmetric hydrogenation using a rhodium catalyst and the Walphos ligand yielded the corresponding β3-amino acid derivatives.
Keywords: Ynamide; Regioselective carbozincation; Asymmetric hydrogenation; Transition metal-catalyzed synthesis; β3-Amino acid derivative